GEOGRAPHICAL ASSESSMENT OF GEO-ECOLOGICAL SITUATION OF THE TERRITORY OF THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
In the article, the geo-ecological situation caused by the use of nature of the territory of the Republic of Armenia is presented, analyzed, interpreted and evaluated from a geographical point of view, based on the methodological framework of territorial synergistic effect and the concept of ecological-economic balance of the territory. The cause-and-effect relationships of the geo-ecological situation and its territorial picture are also presented.
Keywords: geo-ecological situation of the territory of the RA; geo-ecology; nature use; environmental and economic factors; regional environmental politics